Pendidikan Karakter Multikultural Dalam Pembentukan Akhlak Siswa - Nuraini; Fitriani (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2025)
This research is based on the need to improve the moral quality of students at SMP PGRI 32 Kampai Island, considering that their moral condition requires special attention. The aim of this research is to analyze various factors that influence the formation of morals through the implementation of multicultural character education at SMP PGRI 32 Kampai Island, both internally and externally. This research uses a descriptive qualitative approach with questionnaires and interviews as the main tools for data collection. The research subjects involved Islamic Religious Education (PAI) teachers and students at SMP PGRI 32 Kampai Island. Data was analyzed descriptively to describe the various efforts that have been made. The research results show that PAI teachers use a number of strategies, such as providing role models, integrating Islamic teachings in the teaching and learning process, and organizing religious activities, such as recitations and training in group worship. This effort has had a real positive impact on increasing students' faith, morals and piety. The conclusion of this research is that the implementation of multicultural-based education and integrated moral development plays an important role in developing the character of students living in coastal areas.